In the beginning : the Navajo genesis - Levy, Jerrold E., 1930-2002 (University of California Press, 1998)
Jerrold E. Levy's analysis of Navajo creation and origin myths shows convincingly that the Navajo religion is as complete and nuanced an attempt to answer humanity's big questions as are the religions brought to North America by Europeans. Looking first at the historical context of the Navajo narratives, Levy points out that Navajo society has never during its known history been either homogeneous or unchanging, and he goes on to identify in the myths persisting traditions that represent differing social perspectives. Levy also compares Navajo answers to the perennial questions about the creation of the cosmos and human nature with the answers provided by Judaism and Christianity and also by contemporary scientific cosmology. The possibility that Navajo religion will continue to be altered by changing conditions as it has in the past makes this fascinating account all the more timely.